Agriculture Ontology for Meta-analysis (AOM): Livestock Prototype - Rosenstock, Todd S.; Steward, Peter Richard; Joshi, Namita (2024)
An initial version of the Agriculture Ontology for Meta-analysis (AOM) based on Livestock data from Evidence for Resilience Agriculture (v0.0.1beta). This proto-ontology is designed for the annotation of information from peer-reviewed literature that describe livestock diet, pasture management and breed papers. It's generated from over 400 publications in the ERA dataset. The ontology contains links to existing ontologies (such as NCBI, NCIT, FOODON, CHEBI, EOL), agrovoc and feedipedia. The ontology is a living resource that will be regularly updated and we welcome contributions.